Investigation on preparation porous titanium through calciothermic reduction of porous TiO precursors - Zhijun Wang; Baoqiang Xu; Jia Yang; Bin Yang; Heng Xiong; Guobo Yang; Fengkang Wang (Journal of Materials Research and Technology, 2020)
A route is present for preparing porous titanium scaffolds with open and interconnected pore morphology through calcium thermal in-situ reduction of TiO precursor. Titanium and dioxide titanium powders, with ammonium carbonate as the space holder, were used to prepare porous precursor whose main phase is TiO by a sintering process. Then calcium vapor was conduced to reduce the precursor and CaO was removed by leaching to obtain porous titanium structures. The morphology, pore structure, phase analysis of porous titanium precursor and porous titanium scaffolds were investigated by means of XRD, SEM and EDS. The porosity was observed by Archimedes method. By this route, the porous titanium with multi-gradient pore sizes ranging from a few microns to several hundred microns was formed. The porous titanium is of multi-gradient pore size distribution of 100 μm bigger, 10 μm∼100 μm and 10 μm smaller. The micro-pores on the pore walls increases connectivity between the macro-pores throughout the porous titanium interior. The porous titanium obtained by this method has a porosity of 50–65% and a titanium content more than 99%.